2019
DOI: 10.1063/1.5116170
|View full text |Cite
|
Sign up to set email alerts
|

Electrically detected-magnetic-resonance identifications of defects at 4H-SiC(0001¯)/SiO2 interfaces with wet oxidation

Abstract: We present electrically detected-magnetic-resonance (EDMR) identification of major and minor interface defects at wet-oxidized 4H-SiC(000 1)/SiO 2 interfaces for C-face 4H-SiC metal-oxide-semiconductor field-effect transistors. The major interface defects are identified as c-axial types of carbon-antisite-carbon-vacancy (C Si V C) defects. Their positive (þ1) charge state generates a spin-1/2 EDMR center named "C-face defects" and behaves as an interfacial hole trap. This center is responsible for the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…In this paper, we characterize the P bC center at 4H-SiC(0001)/ SiO 2 interfaces in more detail by employing two techniques: one is conventional ESR spectroscopy 12 and another is electrically detected-magnetic-resonance (EDMR) spectroscopy [16][17][18][19] enabling electrical detection of ESR signals. ESR can give us spin densities of the P bC center.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we characterize the P bC center at 4H-SiC(0001)/ SiO 2 interfaces in more detail by employing two techniques: one is conventional ESR spectroscopy 12 and another is electrically detected-magnetic-resonance (EDMR) spectroscopy [16][17][18][19] enabling electrical detection of ESR signals. ESR can give us spin densities of the P bC center.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this limitation is that the characterisation of heterostructures, including buried layers and interfaces within them, presents a challenge for many established characterisation techniques and necessitates the use of very advanced techniques. [10,[15][16][17][18] An established materials characterisation technique that has been applied extensively to the investigation of SiC/SiO 2 structures after nitridation, contributing to our current understanding of the system, is X-ray photoelectron spectroscopy (XPS). [7,13,[19][20][21] We recently showed that soft X-ray photoelectron spectroscopy (SXPS) is a powerful technique to probe the chemical state of the SiC/SiO 2 system.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 4H-SiC/SiO 2 interfaces have been widely studied over two decades; however, the search for benchmark models of their interface defects is still ongoing. [17][18][19][20][21][22][23][24] In this Letter, we present a spectroscopic and theoretical identification of a P b -like interface defect in 4H-SiC MOS systems, which we call the "P bC center." The P bC center is intrinsically formed after thermal oxidation of the 4H-SiC(0001) surface (the Si-face), which is the standard surface of 4H-SiC wafers.…”
mentioning
confidence: 99%
“…We believe that the P bC center is identical to a previous "interface carbon defect" with a typical density of 3-4 Â 10 12 cm À2 observed by electron-spin-resonance (ESR) spectroscopy on thermally oxidized 4H-SiC(0001)/SiO 2 substrates. 17,18 Instead of ESR, we here used electrically detected-magnetic-resonance (EDMR) spectroscopy, [19][20][21][22][23] which enabled us to complete a full analysis of 13 C and 29 Si hyperfine (HF) interactions of this center. Like the P b center in Si/SiO 2 systems, the formation of the P bC center is closely correlated with relaxation of the oxidation-induced strain at 4H-SiC/SiO 2 interfaces, which was quantitatively confirmed from first-principles calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation